Multi Cooperative Information System Using Laravel Framework - Iman, Fadhli Munadi; Tristiyanto, Tristiyanto; Prabowo, Rizky (Universitas Lampung, 2018)
The number of cooperatives in Indonesia became the largest in the world. However, the cooperative only contributes 4% of the Gross Domestic Product. It means most of the cooperative is managed unprofessionally. Many of the cooperatives are closed by the government as there are no annual members meeting and transparency of cooperatives business process. This shows that communication and data transparency in cooperatives is very important. But, the cooperatives are difficult to show data transparancy and communicate with members because there is no media or something to support the communication for develop the cooperative.This research has succeeded in developing Multi Cooperative Information System using Laravel framework. Multi Cooperative Information System can store member data collection, financial transactions, calculating profit sharing, and facilitate communication. This system build based on Software as a Service (SaaS) system so cooperative can subscribe with small amount of fee, ignoring the development and maintaining the system. Â This system already pass the test by black box testing and expert judgement.